Guide, Co-guide, Supervisors as Author in Publication on Student Thesis - Shah, Jay N (Journal of Nepal Health Research Council, 2021)
Good research writing and publication practices are important to identify, acknowledge, and generate awareness for ethical and credible science. Academic requirement for research thesis, and ‘publish or perish’ culture of academia for career evaluation of faculties contribute to authorship misconducts. The authorship criteria have been clearly outlined by international guidelines like International Committee of Medical Journals Editors, Committee on Publication Ethics, Council of Science Editors, World Association of Medical Editors. However, the practice of guide, co-guide as authors in students’ thesis articles continues as inappropriate authorship. This is a topic which requires more debate in academia. Historical practices of academia, the power dynamics, and the guidelines of the journals vary and make this dispute even more complicated. In Nepal, we need to expand the discussion among stakeholders from academia, universities, monitoring bodies, ethical committees to journals for a consensus; to ‘put to rest’ this issue and be in line with the international guidelines.Keywords: Authorship guideline; journal article publication; research thesis guide co-guide supervisor